Spine Fractures in Ankylosing Spondylitis: A Case Report and Review of Imaging as well as Predisposing Factors to Falls and Fractures - Fatemi, Gita (2014)
BACKGROUND: Ankylosing spondylitis (AS), an inflammatory arthritis that affects the axial skeleton, predisposes patients with severe disease to falls and spinal fractures. Advanced imaging has improved the process of fracture detection. In spite of increased knowledge about early diagnosis and management of AS, little attention is being paid to the environmental hazards that pose a risk for patient outcome. OBJECTIVES: To identify risk factors for falls and fractures and evaluate imaging modalities in the detection of fractures in AS patients. METHODS: A case report and review of the literature using PubMed for English articles from 2000 to 2013 regarding AS patients’ risk factors for falls and fractures and imaging modalities used to diagnose fracture in this population. RESULTS: Potential impairments in balance and coordination in the AS population include vestibular dysfunction, thoracolumbar kyphosis, and deficits in proprioception. A common and significant environmental risk factor for falls includes the use of a tub-shower arrangement. Furthermore, osteoporosis is a well-known complication of AS that can predispose to fracture. Lastly, there are no comprehensive studies that have evaluated the ability of advanced imaging modalities to identify an acute spine fracture in this patient population. CONCLUSIONS: AS patients with advanced disease are at increased risk of falls and fractures due to many factors including but not limited to a rigid spine and difficulty with peripheral vision. A tub-shower arrangement commonly found in homes and hotel rooms is a major hazard. A consistent approach to diagnosis of fractures involving advanced imaging recommendations should be considered.